Stochastic groundwater transport flow model in Pontian, Johor - Wong, Chai Yun (2014)
Groundwater is the fresh water contained in aquifers buried below the earth's surface and is becoming vital natural resources for the nation nowadays. The demand of groundwater development in many countries is increases due to the limitation supplies of the fresh water on earth. However, due to the presence of rivers and abundance of rainfall in Malaysia, groundwater is given less priority as a source of water supply. This research studied on the hydraulic conductivity, K which is an important variable in groundwater transport flow. The data used in this study are two sets of secondary data collected by using auger-hole method with 2 different diameter measuring auger-hole near Jalan Sawah, Pekan Nenas, Pontian, Johor. The values of soil hydraulic conductivity were obtained by using Ernst and Hooghoudt formula. From the calculation, the range of hydraulic conductivity is between 0.3457 x 10-3 cm/s to 4.8135 x 10-3 cm/s and it agreed that the hydraulic conductivity of peat soil that is between 1 x 10-4 cm/s to 1 x 10-3 cm/s. Besides that, ths research also studies the effect of depth of water table and radius of auger hole toward hydraulc conductivity. The result obtained from multiple linear regression shows that the depth of water table and radius of auger hole affect teh hydraulic conductivity significantly. Lastly, stochastic approach was used to model the one dimensional, steady state and saturated groundwater flow and the exact solution is the expexted function of the gradient of the head potential.